Mathematical Modeling and Performance Study of Fischer-tropsch Synthesis of Liquid Fuel over Cobalt-silica. (August 2015) - Moazami, Nima; Mahmoudi, Hamid; Panahifar, Pooria; Rahbar, Kiyarash; Tsolakis, Athanasios; Wyszynski, Miroslaw L.
Abstract: A numerical one-dimensional pseudo-homogeneous mathematical model of a fixed bed reactor for Fischer-Tropsch (FT) synthesis was developed over a simulated nitrogen-rich syngas (33% hydrogen, 17% carbon monoxide and 50% nitrogen (volume basis)), on a cobalt-silica catalyst. An algorithm was developed and the MATLAB codes were written in order to predict the product selectivity (H2 O, CO2 and hydrocarbons i.e. CH4, C2, C3, C4 and C5+ ) and syngas conversion (CO and H2 ). In order to predict the kinetic parameters, the global search optimization subroutine (from MATLAB Global Optimization) was used. The model was fitted with experimental data at five different operating conditions with respect to conversion and selectivity. Discrimination between the model and the experiments was determined by the mean absolute relative residuals percentage (MARR %) and the value was 13.29%. The Effects of operating conditions such as reaction temperature, total pressure, flow rate and H2 /CO molar ratio were investigated on the catalytic performance of the cobalt-silica for synthesis of liquid fuel. The model was studied in the range of 200-260 °C, 1-25 bar, reduced gas flow rate (per unit mass of catalyst) of 2.4-3.6 NL gcat -1 h -1 and H2 /CO = 1.75-2.75 (mole basis).